Poverty, segregation and social exclusion of Roma communities in Slovakia - Rochovská, Alena; Rusnáková, Jurina (Bulletin of Geography. Socio-economic Series, 2018)
This paper examines the issue of poverty and social exclusion of Roma in Slovakia. It highlights the problem of poverty among Roma communities, which together with segregation leads to absolute poverty and social exclusion. Based on ethnographic research the paper examines conditions in which inhabitants of segregated Roma communities sustain their livelihoods. In the qualitative part of our research we ask how inhabitants of segregated settlements organize and manage their livelihood and what strategies and practices they use to ensure social reproduction. Further, we assess the articulations between exclusion and social networks and other spheres of assets, including formal and informal labour, state benefits and the use of material assets. We argue that spatial segregation has an enormous impact on poverty.